2016
DOI: 10.3892/ol.2016.4738
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lncRNA NEAT1 mitigates multidrug resistance by inhibiting ABCG2 in leukemia

Abstract: Abstract. Leukemia is a heterogeneous clonal disorder in which early hematopoietic cells fail to differentiate and do not undergo programmed cell death or apoptosis. Less than one-third of adult patients with leukemia are managed using current therapies due to the emergence of multidrug resistance (MDR), emphasizing the need for newer and more robust approaches. Recent reports have suggested that long non-coding RNAs (lncRNAs) contribute to selective gene expression and, hence, could be manipulated effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“… 24 NEAT1 expression level was downregulated in leukemia patients and cells and overexpression of NEAT1-mitigated MDR induced by cytotoxic agent through inhibition of ATP-binding cassette G2 (ABCG2) in leukemia. 25 Another study reported that NEAT1 enhanced cisplatin sensitivity in non-small-cell lung cancer through functioning as a ceRNA to upregulate EGCG-induced cisplatin transporter CTR1 (copper transporter 1) by sponging miR-98-5p. 26 In the present study, it is demonstrated that NEAT1 was upregulated in PTX-resistant ovarian cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“… 24 NEAT1 expression level was downregulated in leukemia patients and cells and overexpression of NEAT1-mitigated MDR induced by cytotoxic agent through inhibition of ATP-binding cassette G2 (ABCG2) in leukemia. 25 Another study reported that NEAT1 enhanced cisplatin sensitivity in non-small-cell lung cancer through functioning as a ceRNA to upregulate EGCG-induced cisplatin transporter CTR1 (copper transporter 1) by sponging miR-98-5p. 26 In the present study, it is demonstrated that NEAT1 was upregulated in PTX-resistant ovarian cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“… 20 NEAT1 dys-regulated in ovarian cancer, lung cancer, gastric cancer and leukemia were reported to contribute to the chemotherapy resistance of paclitaxel, cisplatin, adriamycin, alisertib and bortezomib. 14 , 21 23 LncRNA PVT1, TUG1 and UCA1 were reported to upregulate in UBC, especially in the doxorubicin and cisplatin-resistant UBC tissues and cell lines. Forced lncRNA-LET expression delayed gemcitabine-induced tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NEAT1 expression was found to be repressed in leukemia cells and overexpression of NEAT1 alleviated multidrug resistance in leukemia cells through inhibition of ATPbinding cassette G2. 35 NEAT1 was demonstrated to function as a ceRNA of miR-98-5p to upregulate copper transporter 1 (CTR1), thus enhancing cisplatin sensitivity in lung cancer cells. 36 Additionally, NETA1 was reported to be highly expressed in gastric cancer tissues and cells, moreover, NEAT1 knockdown depressed chemotherapy resistance to adriamycin and promoted adriamycin-induced apoptosis in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%